Hand washing among health workers in tertiary health facilities in Bayelsa State, Nigeria - McFubara, Kalada Godson; Ogbe, Deborah K.; Mbooh, Romeo T.; Nwizia, Baribefii P.; Nasamu, Ughiemosomhi P.; Ogori, Demedongan S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hand washing is a cheap and effective method of preventing nosocomial infections by health workers, but it has not been given strong policy support for resource allocation. Objectives: To describe knowledge, attitude and practice of handwashing among health care workers and to identify the factors affecting the practice in tertiary health care facilities in Bayelsa State. Methods: Four groups of health workers who work directly with patients at the Niger Delta University Teaching Hospital and Federal Medical Centre, both in Yenagoa Local Government Area of Bayelsa state, were studied. A multi-stage sampling was conducted to select 224 respondents. Self-administered and interviewer-administered questionnaires were used to collect data which were then analysed on the Microsoft Excel programme.Response rate of 91.50% (205 respondents) was achieved. Krejcie and Morgan’s sample size formula was used at 95% confidence level. Results: 140 (68.30%) of all respondents had good knowledge of hand washing and about half have excellent hand washing practice. But only 44 (21.5%) had very good knowledge of nosocomial infections. The lack of materials such as soap, water and towels are limiting good hand washing practice. Conclusions: Although there is good knowledge of hand washing and of nosocomial infections as well as good attitude towards hand washing, they have no positive correlation with practice. Inadequate resources may be worsening nosocomial infections. Improved health policy for more health manpower and accessible resources for more regular hand washing are recommended.